Pengaruh Keberadaan Partikel Asing Terhadap Karakteristik Medan Listrik Pada GIS Equilateral Tiga Fasa - Rizki Wahyu Pratama; Hanalde Andre; Umar Khayam (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
This paper analyzes the effect of the presence of foreign particles on an equilateral arrangement of 3 phase gas insulated switchgear (GIS) insulation equipment. In this calculation, the electric field characteristics will be analyzed in 3-phase equilateral GIS by varying the location of the particles in the GIS tank. Particles are modeled to have a length of 5 mm and a thickness of 0.5 mm located in a 3 phase GIS equilateral arrangement with a tank diameter of 150 mm and a conductor diameter of 25 mm. The electric field calculations are reviewed at several points in the 3-phase equilateral GIS tank. The simulation and calculation of the electric field were calculated with FEM method software. The results of the calculations show that there are differences in the characteristics of the electric field between normal GIS and GIS where foreign particles are present. The difference in these characteristics can be seen in the magnitude of the electric field, and the ratio of eccentricity from some point of view. Keywords : gas insulated switchgear, equilateral, foreign particles, electric field, eccentricity ratioAbstrakPaper ini menganalisa tentang pengaruh keberadaan partikel asing pada peralatan hubung isolasi gas/ gas insulated switchgear (GIS) 3 fasa susunan equilateral. Pada perhitungan ini, akan dianalisa karakteristik medan listrik pada GIS equilateral 3 fasa dengan memvariasikan letak partikel dalam tangki GIS. Partikel dimodelkan memiliki panjang 5 mm dan ketipisan 0.5 mm terletak di dalam GIS 3 fasa susunan equilateral dengan diameter tangki 150 mm dan diameter konduktor 25 mm. Perhitungan medan listrik ditinjau pada beberapa titik dalam tangki GIS equilateral 3 fasa. Simulasi dan perhitungan medan listrik dilakukan dengan perangkat lunak menggunakan metode FEM. Hasil dari perhitungan menunjukkan adanya perbedaaan karakteristik medan listrik antara GIS normal dengan GIS yang terdapat partikel asing. Perbedaan karakteristik ini dapat dilihat pada besar medan listrik, dan rasio eksentrisitas pada beberapa titik tinjau keberadaan partikel. Kata Kunci : gas insulated switchgear,  equilateral, partikel asing, medan listrik, rasio eksentrisitas